PENERAPAN PRINSIF PRINCIPLE UTMOST GOOD FAITH DALAM PERJANJIAN ASURANSI - Rusmini, Rusmini (Justici, 2023)
ABSTRACT In implementing the insurance agreement, the principle of Utmost Good Faith or the principle of good faith must be implemented by the insurer and the insurer. The problem in this paper is how to apply the Principle of Utmost Good Fait in insurance agreements. The type of research used in completing this research is a normative juridical research method that is descriptive analysis, namely research conducted by examining library materials (secondary data) or library law research. The application of the principle of good faith in an insurance agreement implies that both parties, namely the insured and the insurer, reciprocally must base the insurance agreement or agreement in very good faith, meaning that they do not hide clear and correct information needed by each party.